1959
DOI: 10.1111/j.2042-7158.1959.tb12624.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Fluorimetric Determination of Adrenaline and Noradrenaline

Abstract: A modification of the fluorimetric method for the determination of adrenaline and noradrenaline in pharmaceutical solutions is described. In this method sulphite present is destroyed with iodine, the added excess of which is reduced with arsenous acid, a manipulation which does not affect the fluorescence obtainable.ADRENALINE and noradrenaline in low concentrations are most suitably determined by the fluorimetric method1#2. In pharmaceutical solutions, sulphite is usually present as a stabiliser. This introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1972
1972

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Yoshinaga (416) found that the ethylenediamine method, although sensitive, lacks specificity. In the Lund procedure using Mn02 oxidation at pH 4 for adrenaline and pH 6 for noradrenaline, precise timing is necessary (79) and other improvements in technique are suggested (100); if sulfite is present, it must first be destroyed (48). Iodine also may be employed as the oxidant, at pH 4.4 and 7.2, respectively (162).…”
Section: Magnesiummentioning
confidence: 99%
“…Yoshinaga (416) found that the ethylenediamine method, although sensitive, lacks specificity. In the Lund procedure using Mn02 oxidation at pH 4 for adrenaline and pH 6 for noradrenaline, precise timing is necessary (79) and other improvements in technique are suggested (100); if sulfite is present, it must first be destroyed (48). Iodine also may be employed as the oxidant, at pH 4.4 and 7.2, respectively (162).…”
Section: Magnesiummentioning
confidence: 99%